Fundamental principles of architectural internal arrangements of space of spiritual-retreat centre - Голубчак, Катерина; Holubchak, Kateryna (Lviv Politechnic Publishing House, 2017)
У цьому дослідженні, на основі аналізу сучасного досвіду архітектурної організації духовно-реколекційних центрів, виявлено основні тенденції та вимоги, що пред'являються до інтер'єрного вирішення цих споруд. Запропоновано принципи та рекомендації для дизайнерів та архітекторів, якими доцільно керуватись при організації внутрішнього простору духовно-реколекційних центрів.

In this research, based on the analysis of the current experience of the architectural organization of spiritual-retreat centers, the main tendencies and requirements for interior design of these structures were discovered. The principles and recommendations for making internal arrangements of space of the spiritualretreat centers are suggested.
Основні засади архітектурної організації внутрішнього простору духовно-реколекційних центрів
Keywords: духовно-реколекційні центри; принципи організації; внутрішній простір; інтер’єр; spiritual-retreat centers; principles; internal arrangements